Pembaptisan Yesus: Peristiwa Trinitaris - Budiarjo, Mikhael Wicaksono (Felicitas, 2023)
The one God is the triune God. This revelation was received with deep faith by Catholics. Historically, this revelation has been a great mystery of faith. Even though it is a mystery, people can still recognize it gradually because God Himself has shown His revelation to witnesses. That testimony was received by the writers of the new covenant scriptures and they have written it down as a historical account of salvation. One of the events of faith that shows the presence of the three divine persons is the story of Jesus' baptism in the Jordan River. The three Synoptic Gospel writers, Matthew, Mark, and Luke, tell the story of Jesus' baptism with different perspectives according to their characteristics but still have similarities in seeing the presence of the Triune God. So, in this work, the author wants to show the trinitarian event or the presence of the three divine persons in the story of Jesus' baptism in the Jordan River as told in the Synoptic Gospels and provide a statement from Church teaching about this baptism of Jesus.